DIGITAL TRANSFORMATION AND MULTIPROFESSIONAL INTEGRATION: NEW PATHWAYS TO PATIENT SAFETY AND SUSTAINABILITY OF HEALTH SYSTEMS - de Oliveira, Dayvison Santos; de Sales, Mariana Elizabeth Lopes; Ferreira, Lauriene Karina Ramos da Costa; Melo, Kárita Roberta da Silva; Santos, Kátia Lamara de Araújo; Araújo, Juliana Botelho; Gomes, Monize Lopes de Araújo; Coutinho, Alynne Cristina Ferreira; Carretilha, Arilana de Jesus; Lopes, Jander Marcus Cirino; Brilhante, Vânia Cristina Ribeiro; Correa, Amanda Emanuele dos Santos; et al. (Seven Editora, 2026)
Digital transformation has significantly reshaped healthcare systems, influencing how care is delivered, managed, and evaluated. In this context, multiprofessional integration emerges as a key element to ensure safe, efficient, and patient-centered care. This study aims to discuss how the incorporation of digital technologies is redefining healthcare models and strengthening collaborative practices among health professionals, with direct implications for patient safety and health system sustainability. This is a qualitative study based on an integrative review of recent national and international scientific literature. The discussion will address key aspects such as telemedicine, remote monitoring, electronic health records, shared decision-making, and the role of different professional groups in delivering coordinated care. While digital transformation expands possibilities and improves care processes, it also presents challenges related to workforce training, system integration, and data security. It is concluded that digital transformation, when combined with effective multiprofessional collaboration, represents a promising pathway toward more resilient healthcare systems capable of delivering comprehensive, safe, and sustainable care.